A Study of Dark (Disaster) Tourism in Reconstructed Barpak, Nepal - Kunwar, Ramesh Raj; Karki, Neeru (The Gaze: Journal of Tourism and Hospitality, 2020)
Barpak is one of the largest and self-reliant villages of Nepal, situated at an altitude of 1900m of Gorkha district the village is popularly known for home-stay based tourism destination in the mountainous region of Nepal. At present, Barpak has been garnering attention as epicenter of Earthquake 2015. The earthquake transformed the former traditional homogeneous architectural attraction into seeming architectural repulsion. There is confusion among the locals about their identity that was predominantly related with their homogeneity. There is an upsurge of cognitive dissonance and locals see the present context as tourism impossibility and are quite hopeless about post-disaster tourism development. This article adapts synchronic approach to highlight the tourism dynamics of Barpak in the aftermath by contemplating on the fact that disaster-led repulsion could be turned into attraction via an alternative paradigm. Developing both dark and non-dark (leisure) attractions that includes sociology of death, beliefs of death and disaster, commoditization of death, mortality mediation, memorials on one side and the landscapes, place, identity, socio-cultural diversity, instant culture in the Aftermath, reconstruction narratives from the locals, on the other side, respectively. A leap from leisure tourism destination to niche tourism destination and continuation of both by complimenting each other. This unique mixture of dark and non-dark products at one place could be a prototype for post-disaster tourist destinations.